Função vascular e autonômica cardíaca em indivíduos hospitalizados com diagnóstico de exacerbação da doença pulmonar obstrutiva crônica, insuficiência cardíaca ou coexistência das doenças e investigação do efeito agudo vascular da ventilação não-invasiva em doentes com insuficiência cardíaca - Schafauser, Nathany Souza (2024)
Chronic Obstructive Pulmonary Disease (COPD) and Heart Failure (HF) often coexist in the same individual and independently are associated with systemic inflammation and increased cardiovascular risk, with a worse prognosis when combined. During COPD exacerbations (ECOPD), there is an aggravation of inflammation, oxidative stress, and endothelial dysfunction, contributing to increased vulnerability to cardiovascular complications. Similarly, decompensation of HF is marked by acute deterioration of the clinical condition with intensification of signs and symptoms of pulmonary and/or systemic congestion, associated or not with worsening tissue perfusion. During periods of greater stability, evidence points to impairment in aspects such as arterial stiffness, endothelial function, and cardiac autonomic modulation (CAM) in both diseases, but there is still a gap regarding this more comprehensive cardiovascular approach during exacerbation and hospitalization, as well as the influence of HF comorbidity during ECOPD. Additionally, the use of non-invasive ventilation is indicated in the treatment of decompensated HF (DHF). NIV in patients with HF has been shown to improve ventricular function, increase intrathoracic pressure, and cardiac output. However, it is still unknown whether these hemodynamic improvements translate into improved endothelial function. STUDY 1 - OBJECTIVE: To investigate the cardiovascular profile of hospitalized patients with ECOPD in the presence of HF and compare it with isolated forms of COPD and HF. METHODS: Cross-sectional study including patients diagnosed with ECOPD and decompensated HF (DHF), divided into 3 groups: COPD, COPD-HF, HF. evaluated between 24 and 48 hours after hospital admission. The comprehensive cardiovascular assessment included: 1. Endothelial function: flow-mediated dilation (FMD) methods; 2. Arterial stiffness and hemodynamic variables by pulse wave analysis and carotid-femoral pulse wave velocity (cfPWV); and 3. CAM by heart rate variability analysis. RESULTS: Patients were allocated to groups according to diagnosis as follows: COPD, n = 12; COPD-HF, n = 21; HF, n = 21. In our sample, the mean FMD was 4.45%, indicating endothelial dysfunction. However, in the group with both diseases coexisting, a worse FMD (%) was observed, as presented sequentially for COPD, COPD-HF, and HF. FMD: 5.47 (3.96 – 6.91); 2.66 (0.09 – 3.48); 4.60 (2.30 – 6.43) in % p<0.0005). Augmentation Index (AIx: 29 (19 – 42.6); 34.6 (24.3 – 43.25); 14.5 (8 – 24) p<0.007; cfPWV: (6.5 (5.4 – 7.2); 7.7 (7.0 – 8.5); 6.05 (5.02 – 6.52) in m/s); The COPD-HF group showed greater sympathetic modulation compared to isolated diseases (SNP: -1.32 (-2.53 – -0.62); -2.33 (-2.60 – -2.12); -1.32 (-1.42 – -1.01) p<0.006; SNS: 3.5 (1.40 – 8.55); 7.11 (5.70 – 8.29); 2.32 (1.78 – 5.01) p<0.009). Other indices rMSSD, NN50, pNN50, and TINN also indicate worse CAM in the ECOPD-HF group compared to isolated COPD and HF. CONCLUSION: Vascular function and CAM are more impaired in patients with the comorbidity of HF present in COPD compared to isolated forms of HF and COPD. STUDY II - OBJECTIVE: To investigate the acute effect of NIV on endothelial function in patients hospitalized for DHF. METHODS: Quasi-experimental study including n=20 patients diagnosed with ADHF approached between 24 and 48 hours after hospital admission. The application of NIV lasted between 30 and 60 minutes, using inspiratory pressure between 8 and 12 cmH2O and expiratory pressure between 5 and 7 cmH2O, according to patient tolerance. Before NIV, the following assessments were performed: (1) complete blood count, C-reactive protein, N-terminal pro-B-type natriuretic peptide, and arterial blood gas analysis; and (2) endothelial function, using ultrasound of the brachial artery by the flow-mediated dilation method. Immediately after NIV, the assessments were repeated. The analysis considered the response of flow-mediated dilation after NIV (Δ FMD = FMDpost - FMDpre) and compared the subgroups according to the response in non-responders (ΔFMD < 1.79%) vs. responders (ΔFMD > 1.79%). RESULTS: After NIV, an increase in FMD was observed (4.27 ± 2.51% vs. 6.01 ± 2.80%, P < 0.001), with no significant change in arterial blood gas (p>0.05). In the comparison of non-responders versus responders’ subgroups, patients with lower endothelial response after NIV (ΔFMD < 1.79%) showed higher levels of eosinophils (222 ± 74.8 mm3 vs. 101 ± 24 mm3; p=0.002) and C-reactive protein (7.7 ± 10.17 mg/dl vs. 1.94 ± 2.13 mg/dl; p = 0.021). CONCLUSION: The application of NIV acutely improves endothelial function in patients with DHF. The acute unresponsive effect of NIV on endothelial function in patients with DHF may reflect a negative influence of inflammatory markers.